Design of Sub-surface Constructed Wetland for Greywater Treatment Using Canna Indica (Case Study: Kelurahan Keputih Surabaya) - Athif Husnabilah; Bieby Voijant Tangahu (Institut Teknologi Sepuluh Nopember, 2017)
Untreated greywater is one of sanitation issues that occured in Keputih, Surabaya. In order to manage this sanitation issues, constructed wetland is capable of treating domestic wastewater especially greywater, therefore this method is chosen. Design of constructed wetland is projected for 2019 until 2028 usage. Characteristics of greywater influent is typically: BOD 190,43 mg/l; COD 289,17 mg/l; TSS 206,67 mg/l. Canna indica is selected for this treatment due to maintenance value. Apart from constructed wetland design, standard operating procedure and bill of quantity is also made. From this design, the grewater effluent quality is estimated: BOD 30 mg/l; COD 46,28 mg/l; TSS 26,67 mg/l thus meet the Domestic Wastewater Quality Standard from East Java Governor Regulation No. 7 2013. The cost required to build CW in Kelurahan Keputih Surabaya is Rp 9.156.412.000.